A sociocultural perspective on elderly caregiving - Ahmad, Nobaya (Institute of Islam Hadhari, Universiti Kebangsaan Malaysia; together with Faculty of Human Ecology, Universiti Putra Malaysia; and Department of Islamic Development Malaysia, 2015)
Elderly care giving has always been an issue in countries that is becoming an aged society. However, caregiving has always been the traditional and cultural role of the women specifically the daughters. Many studies locally and globally, have shown that when it comes to care giving, women have been playing an important role in ensuring the welfare of the children, family and elderly is taken care of. The role of caregiving has always been associated with the nurturing role of women. With more women in the workforce in recent times, the role of caregiving for the elderly has taken a turn in the form of services provided by the public and private sector like nursing and elderly residential homes. Issues like the lack of such homes to provide care and the role of other members of the family in the care of the elderly often arise. Contrary to the views in the western society, sending the elderly to be care for in nursing homes and residential care is still not widely accepted in the culture of the society in the east. Hence, the issue of who should care for the elderly is still a matter of concern for the Asian community. What role does the other members of the family play in care giving to the elderly? In Islam, the role of caring for the elderly is clearly specified in many Surahs and the role as describe in the surah does not differentiate between men or women in terms of care giving for the elderly. Hence, the aim of the paper is to highlight issues on caregiving as practiced in many communities, east and west, and discuss the role of men and women in caregiving for the elderly as outlined in Islam.